1992
DOI: 10.1128/aac.36.10.2342
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of ramoplanin against antibiotic-resistant enterococci

Abstract: Ramoplanin, a new lipoglycodepsipeptide antibiotic, was uniformly active against 65 strains of enterococci, including strains higly resistant to vancomycin, penicillin G, and gentamicin. MBCs were usually within a fourfold dilution of the MICs. In time-kill studies, ramoplanin alone demonstrated dose-dependent bactericidal activity against enterococcal strains that resisted killing by vancomycin or penicillin in combination with gentamicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…In all investigations, all strains of all species, including vancomycin-resistant E. faecalis and E. faecium, were inhibited by 8 g/ml and the MIC 90 s (in all but one study) ranged from Յ0.25 to 1.6 g/ml (18,54,132,170,234). Ramoplanin is also bactericidal for enterococci, with the MBCs being only fourfold higher than the MICs (132). Ramoplanin inhibits cell wall synthesis by acting at the level of lipid-intermediate formation, whereas vancomycin and daptomycin interfere with peptidoglycan synthesis by preventing transglycosylation (223).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In all investigations, all strains of all species, including vancomycin-resistant E. faecalis and E. faecium, were inhibited by 8 g/ml and the MIC 90 s (in all but one study) ranged from Յ0.25 to 1.6 g/ml (18,54,132,170,234). Ramoplanin is also bactericidal for enterococci, with the MBCs being only fourfold higher than the MICs (132). Ramoplanin inhibits cell wall synthesis by acting at the level of lipid-intermediate formation, whereas vancomycin and daptomycin interfere with peptidoglycan synthesis by preventing transglycosylation (223).…”
Section: Treatmentmentioning
confidence: 99%
“…In preliminary studies, ramoplanin has been poorly tolerated following intravenous or intramuscular injection, and it seems unsuitable for systemic use because of its toxicity; however, it is being developed for topical use (261). It has been suggested that ramoplanin could be used for the clearance of glycopeptide-resistant enterococci from the gastrointestinal tract (132), and it might well be used to eradicate C. difficile without a risk of colonization by glycopeptide-resistant enterococci (22).…”
Section: Treatmentmentioning
confidence: 99%
“…Ramoplanin is a lipoglycopeptide antibiotic which inhibits peptidoglycan synthesis by inhibiting the formation of lipid intermediate 11 (18). Cross-resistance between these drugs and older peptide antibiotics does not routinely occur (4,11,12). Therefore, these newer peptide antibiotics may retain activity against vancomycin-resistant strains.…”
mentioning
confidence: 99%
“…Ramoplanin is a new lipoglycopeptide antibiotic with activity against most gram-positive organisms (2,17), including enterococci resistant to penicillin or vancomycin (11). Bactericidal activity against a small number of vancomycin-resistant enterococci has been demonstrated elsewhere (4,11).…”
mentioning
confidence: 99%
“…1) is a promising candidate to replace vancomycin. Produced by fermentation of Actinoplanes ATCC 33076, ramoplanin A2 is highly active against numerous Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) (2-6), vancomycin-resistant Enterococcus faecium (VRE), and those resistant to ampicillin and erythromycin (6)(7)(8)(9)(10)(11). Ramoplanin factor A2 is currently under Phase III clinical development for eradication of VRE and MRSA.…”
mentioning
confidence: 99%